ANALISIS PEMBUKTIAN PERJANJIAN SEWA MENYEWA GUDANG SECARA LISAN DALAM PUTUSAN MAHKAMAH AGUNG REPUBLIK INDONESIA NOMOR 2368 K/PDT/2019 - Kenny Joshua; Endang Pandamdari (Jurnal Hukum Adigama, 2021)
Whereas in the lease agreement, both oral & written, there are elements that must be carried out by the respective parties that bind themselves to one another, where if one of the parties does not fulfill its obligations as agreed in the beginning, then the act will cause default. This thesis discusses the warehouse lease agreement which was carried out verbally that occurred in Mempawah City. Making a verbal agreement is a habit of the people in the area because they prioritize their trust in each other. The problem raised in this thesis is the proof of the warehouse lease agreement which is carried out orally. In the court of first instance and the appeal level the oral agreement was declared invalid and could not be proven. Then in the Decision of the Supreme Court Court Number 2368 K / Pdt / 2019, then the oral agreement was declared valid and the defendant was declared default. The form of research in this thesis is normative legal research with qualitative and descriptive methods. This study concludes that an oral agreement based on the concept of contract law adopted by Indonesia is indeed valid and binding once there is an agreement so that the oral agreement in the case can be said to be valid. Meanwhile, the statu